ANALYSIS OF THE ROLE OF THE SCHOOL COMMITTEE IN SDN INPRES 3 TONDO - Pahriadi Pahriadi; Fitryana Puspitasari; M Mahfud (Education Journal, 2020)
This research at investigating the role of the school committee at SDN Inpres 3 Tondo. This research employs a qualitative and descriptive method. The techniques of data collection are observation, interview, and documentation. The research subjects are a member of the school committee, school principal/vice principal, teachers, and community members. The results indicate that; a) the school committee as an advisory board plays a role in planning the school programs, and developing vision, mission, and fundamental aims of the school; b) the school committee as supporting body plays a role in establishing a good cooperation between school and parents, provide school infrastructure and facilities; c) the school committee as a controlling body plays a role in supervising the teachers’ performance, monitoring the school organization and controlling school outputs; d) The school committee as a liaison body plays a role in disseminating school programs and policies to the community, creating cooperative relationships between parents and schools